The benefit and risk of misoprostol use: in obstetrics and gynecology - Sufi Desrini (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2015)
Misoprostol is licensed to treat gastric ulcers but now it is widely used for a variety of indications in osbtetrics and gynecology. This is called ‘off-label’ use. Misoprostol is cheap, stable at room temperature and easily to access it. Available in tablet form, it can be administred vaginally, rectally, sublingually and bucally. This review explains benefit and risk of misoprostol in obstetric and gynecology field.